Stable international environmental agreements: An analytical approach - Effrosyni Diamantoudi; Eftichios S. Sartzetakis (Fondazione Eni Enrico Mattei (FEEM), 2002)
In this paper we examine the formation of International Environmental Agreements (IEAs). We provide an analytical treatment of the main model used in the literature and offer a formal solution of it (which has not been available so far), while we clarify some misconceptions that exist in the literature. We find that the unique stable IEAs consist of either two, three or four signatories if the number of countries is greater than or equal to 5. Furthermore, we show that the welfare of the signatories of a stable IEA is very close to its lowest level vs the welfare of signatories of other non-stable IEAs. While in our model countries' choice variable is emissions, we extend our results to the case where the choice variable is abatement efforts.
Keywords: 330; Umweltabkommen; Internationale Umweltpolitik; Theorie